When more is less: The role of cross-functional integration, knowledge complexity and product innovation in firm performance - Perez-Luno, Ana (My University, 2019)
Purpose: The purpose of this paper is to analyze the role of a specific mechanism for cross-functional integration (CFI) in the relationship between product innovation and firm performance. It takes a contingency perspective, accounting for how these relationships vary depending on the degree of organizational knowledge complexity. Design/methodology/approach: Hypotheses are tested via regression analysis with interaction effects in a sample of 105 wineries from Spain, using both objective and subjective firm performance data. Findings: The results obtained confirm the existence of significant triple interaction effect of CFI, knowledge complexity and product innovation on firm performance. CFI has a negative moderating effect on the relationship between product innovation and performance and this effect varies according to the degree of organizational knowledge complexity. Research limitations/implications: This paper looks at variables that have been hitherto studied at the project or product level, at the firm level, in an attempt to untangle the relationship between innovation, CFI, knowledge complexity and firm performance. Study’s main limitations lie in the use of a cross-functional design and its focus on a single industry. Practical implications: Firms dealing with complex organizational knowledge could use this CFI mechanism in the development of new products when their size and resources do not allow the creation of more formal temporal structures, such as cross-functional teams. However, unless the winery has to deal with a high degree of knowledge complexity, involving the oenologist in several functional areas for the purpose of coordination, may detract resources from product innovation effort and lead to a poorer performance. Originality/value: This study showcases a mechanism of CFI not explored in previous research, but used in practice at many firms, i.e. the cross-pollination of ideas across different functional areas through the participation of the responsible for the product development, and tests its role in the relationship between product innovation and different types of firm performance.
PUBLISHED
Keywords: Product innovation, Firm performance, Knowledge complexity, Cross-functional integration; Creative Technologies; Innovation